THE INFLUENCE OF E-SERVICE QUALITY, PRICE FAIRNESS, AND PERCEIVED EASE OF USE ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION IN ONLINE FOOD DELIVERY - Azizi, Muhammad Abid; Rizan, Mohamad; Febrilia, Ika (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
This research tested the mediating role of customers' satisfaction between e-service quality, price fairness, and perceived ease of use on repurchase intention. The data collection method utilized a survey instrument in the form of a questionnaire. This study collected a research sample of 230 users from Jakarta, Indonesia, who had made transactions on an online food delivery app at least five times in the last month. This study used SPSS version 27 and SEM (Structural Equation Model) from the LISREL software version 8.80 to process and analyze research data. The results suggest that e-service quality, price fairness, and perceived ease of use have a significant positive effect on customer satisfaction. The results also indicate a significant positive impact of price fairness and perceived ease of use on repurchase intention. Meanwhile, e-service quality has no effect on repurchase intentions. This study also found that e-service quality, price fairness, and perceived ease of use have a positive effect on repurchase intention through customer satisfaction in the online food delivery app services industry.